2019
DOI: 10.1186/s12888-019-2196-2
|View full text |Cite
|
Sign up to set email alerts
|

The Herts and Minds study: feasibility of a randomised controlled trial of Mentalization-Based Treatment versus usual care to support the wellbeing of children in foster care

Abstract: Background There is a lack of well-designed randomized controlled trials (RCTs) to investigate the efficacy of psychological therapies for children in foster care with emotional and behavioural difficulties. Mentalization-based therapy (MBT) focuses on supporting the carer-child relationship by promoting reflective capacity. This study examined the feasibility and acceptability of an RCT of MBT, delivered in a family-format, for children who are in foster care in the UK. Method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 22 publications
0
24
0
Order By: Relevance
“…Two of four subscales on a measure of children's reaction to parental conflict evidenced large intervention effects (d = 1.35-1.63). Midgley et al (2019a) reported no significant improvement on foster-carerreported measures of child emotional and behavioural difficulties compared to those in the TAU. In contrast, child reported measures indicated significant improvements at 12 and 24 weeks, respectively, with medium effect sizes noted.…”
Section: Psychological Outcomesmentioning
confidence: 80%
See 1 more Smart Citation
“…Two of four subscales on a measure of children's reaction to parental conflict evidenced large intervention effects (d = 1.35-1.63). Midgley et al (2019a) reported no significant improvement on foster-carerreported measures of child emotional and behavioural difficulties compared to those in the TAU. In contrast, child reported measures indicated significant improvements at 12 and 24 weeks, respectively, with medium effect sizes noted.…”
Section: Psychological Outcomesmentioning
confidence: 80%
“…Bammens et al (2015) and Adkins et al (2018) assessed parental RF using the five minute speech sample (FMSS; Magaña-Amato, 1983) coded for RF using the RF scale (Fonagy et al, 1998) in their respective analysis of the Family Minds programme for foster and adoptive parents. Midgley et al (2019a) used the FMSS for foster parents but it was not reported as an outcome measure in the study. Finally, Midgley et al (2019b) used the PRFQ and an 8-item RFQ.…”
Section: Resultsmentioning
confidence: 99%
“…Mothers with a borderline personality disorder, for example, may be supported by enhancing their capacities for mentalization and empathy. This applies to foster families as well (Midgley et al ., 2019).…”
Section: A Focus On Prevention: Identifying (And Evaluating) New Oppomentioning
confidence: 99%
“…Economic measures include a version of the Child and Adolescent Service Use Schedule (CA-SUS) designed and tested for use with Children in Care in an earlier feasibility study [39,40] and the Child Health Utility 9 Dimensions (CHU9D) measure of health-related quality of life [41], proxy reported by foster carers.…”
Section: Economic Evaluation Measuresmentioning
confidence: 99%